1993
DOI: 10.1093/clinids/17.3.466
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Staphylococcus aureus Nasal Carriage in Health Care Workers: Analysis of Six Clinical Trials with Calcium Mupirocin Ointment

Abstract: Six double-blind, independently randomized studies evaluated the efficacy and safety of calcium mupirocin ointment in eliminating nasal carriage of Staphylococcus aureus among health care workers. Healthy volunteers with stable nasal carriage of S. aureus (n = 339) received either calcium mupirocin ointment (n = 170) or an identical placebo ointment (n = 169) intranasally for 5 days. Nasal carriage was eliminated 48-96 hours after completion of treatment in 130 (91%) of 143 evaluable volunteers receiving mupir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
2
8

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(84 citation statements)
references
References 29 publications
3
71
2
8
Order By: Relevance
“…A topic bacterial agent has been used to eradicate nasal cavities, armpits, groins and in the hands of patients and health workers. Through this measure, we could reduce the infection rates among patients that will undergo surgeries (26) .…”
Section: Discussionmentioning
confidence: 99%
“…A topic bacterial agent has been used to eradicate nasal cavities, armpits, groins and in the hands of patients and health workers. Through this measure, we could reduce the infection rates among patients that will undergo surgeries (26) .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the risk of infection in deep tissues of the surgical site in Mupirocin-treated patients was five times less than the control group (11). In a large scale study, 91% successful eradication of S. aureus carriers with Mupirocin has been reported (12). Different results have been reported on the effectiveness of eradicating carriers in prevention of surgical, orthopedic and cardiac surgery wound infections, while Gernaat and Kluytmans studies clearly demonstrated that treatment with Mupirocin could significantly decrease postoperative infections (13,14).…”
Section: Methodsmentioning
confidence: 98%
“…Selective suppression and/or eradication of MRSA carriage using mupirocin has been used adjunctively to help control spread of MRSA, 32 " 38 but successful eradication is sometimes transient. Doebbeling et al 39 reported that 26% of patients were recolonized within 4 weeks after decolonization, and 48% of patients who underwent an eradication protocol were culture positive for MRSA after 6 months. 40 Use of mupirocin to eradicate MRSA colonization was studied in a randomized, controlled trial involving colonized hospital patients in Switzerland.…”
Section: Several Studies In This Issue Of Infection Control and Hospitalmentioning
confidence: 99%
“…Hospital-wide rates of MRSA HAI were not reported; perhaps eradication with mupirocin merely delayed the onset of MRSA infection, and so it would not be reflected in the reported rate of MRSA HAIs in the ICU. Because recolonization has been reported, 39 ' 40 it would have been useful to follow up the decolonized cohort longitudinally and assess MRSA colonization and infection status.…”
Section: Several Studies In This Issue Of Infection Control and Hospitalmentioning
confidence: 99%